The Curlytops at Cherry Farm - Garis, Howard Roger, 1873-1962; Greene, Julia (Salt Lake City, UT : Project Gutenberg, 2024)
"The Curlytops at Cherry Farm: Or, Vacation Days in the Country" by Howard R. Garis is a children's novel written in the early 20th century. The story centers around the Curlytops, siblings Teddy and Janet Martin, who are eagerly anticipating their summer vacation at their grandpa's farm. The narrative blends adventure with humor and mischief, featuring characters like their baby brother Trouble, who frequently gets into amusing predicaments. The beginning of the story introduces Ted and Janet as they prepare for their summer vacation, characterized by playful sibling banter and a focus on having fun. After some light-hearted chaos involving hair combing and a muddy escapade with Trouble, the children discover their excitement about going to the famed Cherry Farm, which is filled with delightful cherry trees. However, their mother reveals that there may be trouble regarding the farm, setting the stage for the children$1 (Bs summer adventures amidst their worries about their grandparent's financial struggles. This charming opening engages readers with its playful tone, setting up a mix of fun and familial themes that will likely appeal to young readers. (This is an automatically generated summary.)s
Release date is 2024-02-21
David Edwards, David E. Brown, and the Online Distributed Proofreading Team at https://www.pgdp.net
Keywords: Dogs -- Juvenile fiction; Siblings -- Juvenile fiction; Grandparents -- Juvenile fiction; Domestic animals -- Juvenile fiction; Farms -- Juvenile fiction